The Effect of Flash Sale, Cashback and Free Shipping on Muslim Consumer Consumptive Behavior (Study on Users of the Shopee Application in Aceh) - Wahyudi; T. Meldi Kesuma; Dara Amanatillah (Universitas Darussalam Gontor, 2023)
Consumptive behavior is excessive consumption behavior without being based on need, which prioritizes wants and desires at all times. This study was conducted with the aim of knowing the effect of Flash Sale, Cashback and Free Shipping on Muslim Consumer Consumptive Behavior (Study on Shopee Application Users in Aceh). This study uses quantitative data consisting of primary and secondary data, primary data, namely by distributing questionnaires to 120 respondents. In proving and analyzing the data, the validity test, reliability, classical assumption test, multiple linear regression test and F test (simultaneous) and T test (partial) are used. The results showed that the flash sale variable partially had a significant effect on the consumptive behavior of Muslim consumers using the Shopee application in Aceh. The cashback and free shipping variables partially have no effect and are significant on the consumptive behavior of Muslim consumers who use the Shopee application in Aceh. The flash sale, cashback and free shipping variables simultaneously have a significant effect on the consumptive behavior of Muslim consumers who use the Shopee application in Aceh.